Supratentorial and Infratentorial Located Cavernous Hemangioma: Case Report - Bozgeyik, Zülkif; Akbaş, Gökhan; Kocaöz, Özgür; Oğur, Erkin (Fırat University, 2005)
Cerebral cavernous hemangioma is rare hamartomas of vascular structures. It is mostly seen in the supratentorial region, but also in the infratentorial region. It is usually asymptomatic, but may cause epilepsy, focal neurologic signs and headache. Nowadays, the most valuable diagnostic test in imaging and evaluation of cavernous hemangiomas is MRI. The lesions are smooth bordered and on T1WI and T2WI images central region is seen in mixed and increased signal intensity. Due to hemosiderin deposits, peripheric region shows decreased signal intensity. Our case differs from the cases presented in the literature, because it has infratentorial involvement beside multiple supratentorial lesions.©2005, Fırat Üniversitesi, Tıp Fakültesi

Serebral kavernöz hemanjiom vasküler yapıların nadir görülen hamartomudur. Daha çok supratentoryumu tutar, infratentoryal tutulum daha nadirdir. Genellikle asemptomatik olup epilepsi, fokal nörolojik belirtiler ve baş ağrısı gibi semptomlar da görülebilir. Kavernöz hemanjiomların görüntülenmesinde ve değerlendirilmesinde MR inceleme günümüzde kullanılan en güvenilir tanı yöntemidir. Lezyonlar iyi sınırlı olup santral kısmı T1A ve T2A imajlarda mix sinyal intensitesinde ve genellikle artmış sinyal intensitesi gösterirler. Periferik kısmı hemosiderin depositleriyle ilişkili olarak azalmış sinyal intensitesi gösterir. Olgumuz multipl supratentoryal lezyonların yanı sıra infratentoryal tutulumun da birlikte görülmesi nedeniyle literatürdeki sunumlardan farklılık göstermektedir. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Supratentoryal ve İnfratentoryal Yerleşimli Kavernöz Hemanjiom: Olgu Sunumu